Reclamation, Management and Production Potential of Coastal Saline Soils of Maharashtra - PATIL, K. D.; VAIDYA, K. P.; BORSE, D. K.; GANGAN, S. S.; CHAVAN, L. S. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
The extent of coastal saline soils is 65,000 ha in Maharashtra. Low productivity of coastal saline soil is mainly due to salinity, even though the soils are fertile. The reclamation of coastal saline soil can be carried out by providing and maintaining embankment, surface, subsurface drainage, providing surface dugout ponds and cultural practices. Salt removed by sub surface drainage revealed that salt removal was related to spacing of drains, closer the drains more salt removal. Due to construction of dyke, excavating the drains, horizontal and vertical desalinization reduces soil salinity. Salt tolerant rice varieties PNL – 1, 2, 3 are adopted by farmers of the region. Application of recommended NP + 15 t ha-1 FYM produced significantly higher rice yield and help to reduce soil salinity. Application of organic manures, green manures observed to reduce the adverse effect of salinity on crop. Application of Urea, DAP briquettes found beneficial in reducing the N and P dose by 50%. The stored rainwater in surface dug out pond can be used as protective irrigation for short duration and salt tolerant crops like spinach, radish, mustard, linseed, sugar beet, tomato, cucurbitaceous vegetables and to reduce soil salinity. Simultaneously culturing fish in field and in the ponds is extensively adopted and proving profitable farming in the region.